The Relationship Between Serum Uric Acid Levels and β-Cell Functions in Nondiabetic Subjects - Shimodaira, M.; Niwa, T.; Nakajima, K.; Kobayashi, M.; Hanyu, N.; Nakayama, T. (Hormone and Metabolic Research, 2014)
High serum uric acid (UA) levels are believed to be an independent risk factor for the development of diabetes. We aimed to investigate the relationship between serum UA concentrations and early-phase insulin secretion following a 75 g oral glucose tolerance test (OGTT) in nondiabetic subjects. We enrolled 570 Japanese subjects (354 males and 216 females, aged 50.5±8.9 years and 52.6±7.3 years, respectively), who underwent the 75 g OGTT during their annual health examination. The OGTT confirmed their nondiabetic status. Insulin secretion was estimated by the disposition index (DI) [(Δ insulin/Δ glucose (0–30 min)×(1/HOMA-IR)], which is an adjusted measure of β-cell function relative to variations in insulin sensitivity. Simple linear regression analysis showed negative correlations between serum UA levels and DI, when examined in the whole study population and female subjects only (r=−0.209, p<0.001 and r=−0.232, p<0.001, respectively). However, in male subjects, UA levels did not correlate with DI. In females, multivariate linear regression analysis revealed that serum UA levels were the major predictors of DI, explaining 16.4% of its variation (p<0.001). Serum UA levels significantly correlate with early-phase insulin secretion in nondiabetic Japanese women. It may be an independent risk factor for predicting β-cell function in women.
Keywords: diabetes; disposition index; hyperuricemia; insulin secretion